El problema de la eternidad del mundo en Siger de Brabante - Larre, Olga Lucía (Sapientia, 2013)
the second entry of Aristotle in the Western world brought about a true intellectual revolution. Along with the works of Aristotle, were also introduced Latin translations of Averroes, Philosopher Commentator per excellence. In this way, new themes were incorporated to the Parisian university environment and daily work of thinkers, some of them of controversial nature on revealed truth: among them the issue of the eternity of the world. Our work is focused on the treatise De Aeternitate Mundi by Siger of Brabant in which the author refers to the eternity of the species rather than the eternity of the world. He discusses whether or not there may be creation of the human species in a first human being Adam, or whether the human species must be considered eternal. However, the text has been read in an interpretative key that affects the dogma of creation